PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT PADA MATERI TATA SURYA DALAM UPAYA MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS VII SMP - Fahrun Nisa; Mitri Irianti; Fakhruddin Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The learning devices developed are learning devices based on the cooperative type teams games tournament on solar system material in improving cognitive learning results of VII grade junior high school students, consisting of Learning Implementation Plans (RPP) and Student Worksheets (LKPD). The purpose of this research was to design, develop, and validate learning devices based on the cooperative model type teams games tournament on solar system material. This type of research is Research and Development (R&D) with a 4D model design. The research instrument used was the RPP and LKPD’ validation assessment sheets which was used by the validators to assess learning devices. Data analysis in this research used descriptive analysis, by calculating the validity score of each learning indicator. Based on the results of the validity data analysis, the average value of the validity of the RPP for meeting 1, meeting 2, and meeting 3 is 3.39, 3.42, and 3.4 with a very high category. The average validity of the LKPD components of solar system, planetary movement, and rotation, revolution, & eclipses is 3.27, 3.3 and 3.34 with a very high category, so that the overall average of learning devices is 3.35 with a very high category. Thus, the learning devices based on the cooperative model type teams games tournament were declared valid and suitable for use in solar system material in improving cognitive learning results of VII grade junior high school students.Keyword: Learning Devices, Cooperative Model Type Teams Games Tournament, Solar System Material, Cognitive Learning Results.